Prevalence, risk factors and emergence of extended-spectrum β-lactamase producing-, carbapenem- and colistin-resistant Enterobacterales isolated from wild boar (Sus scrofa) in Tunisia. (February 2022) - Selmi, Rachid; Tayh, Ghassan; Srairi, Sinda; Mamlouk, Aymen; Ben Chehida, Faten; Lahmar, Samia; Bouslama, Mongi; Daaloul-Jedidi, Monia; Messadi, Lilia
Abstract: Antimicrobial resistance (AMR) is recognized as an emerging and growing public health problem worldwide. In Tunisia, knowledge is still limited to domestic animals and humans, and only few data are available regarding the role of wildlife. This research determined the antibiotic susceptibility profiles of Beta-lactamase producing Gram-negative bacteria isolated from the faeces of 110 wild boars ( Sus scrofa ) in northern Tunisia. Fecal samples, obtained post mortem from boar carcasses, were cultured on MacConkey agar and MacConkey agar containing 2 mg/L of cefotaxime. A total of 102 Enterobacterales isolates were identified from 94(85%) fecal samples. Escherichia coli (56, 54%), Citrobacter freundii (14, 13%), Klebsiella oxytoca (11, 10%), and Klebsiella pneumoniae (7, 6%) were the most predominantly identified Enterobacterales. However, Pantoea spp. (4, 4%), Enterobacter spp. (3, 3%), Enterobacter cloacae (1, 1%), Enterobacter gergoviae (2, 2%), Proteus mirabilis (2, 2%), Yersinia sp. (1, 1%), and Citrobacter diversus (1, 1%) were rarely identified. Antimicrobial susceptibility tests revealed that 55% (57/102) of the identified strains were multidrug resistant (MDR). A total of 30% (31/102) of the tested isolates were recognized as Extended Spectrum β-Lactamase (ESBL)-producing strains and bla CTX-M-G1, blaTEM, blaSHV β-lactamases were the main encoding genes revealed. Furthermore, identified isolates showed a high level of AMR, especially for amoxicillin-clavulanic acid (77.67%), ticarcillin-clavulanic acid (71.85%), streptomycin (76.69%), amoxicillin (75.73%), and cephalotin (74.76%). Alarming levels of resistance to colistin (2.9%) and ertapenem (9.7%) were revealed and confirmed by the detection of mcr-1, and bla IMP and bla VIM genes, respectively . Various phenotypes of AMR were obtained in this study highlighting the important role of wild boars as hosts and even carriers for several resistant Enterobacterales isolates. This may represents a focal risk factor allowing the transmission of these strains between domestic, wild animals, environment and humans. Highlights: A total of 102 Enterobacterales isolates were identified in 85% of wild boar's fecal samples. Among the identified Enterobacterales strains, 55% were multidrug resistant. A total of 30% of the tested isolates were recognized as ESBL-producing strains and bla CTXM - G1, bla TEM, bla SHV β-lactamases were the main revealed encoding genes. Alarming levels of resistance to colistin (2.9%) and ertapenem (9.7%) were revealed and confirmed by the detection of mcr-1, and bla IMP and bla VIM genes, respectively. Various phenotypes of AMR were obtained in Enterobacterales strains isolated from wild boar for the first time in Tunisia.